Pengaruh Kepribadian Dan Pengetahuan Kewirausahaan Terhadap Minat Berwirausaha Pada Mahasiswa - Tutut Suryaningsih; Titis Mia Agustin (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2020)
This study aims to find out: (1) The influence of personality on entrepreneurship interests (2) The influence of entrepreneurial knowledge on entrepreneurship interests (3) The influence of personality and entrepreneurial knowledge on the interest in VIII semester student entrepreneurship in Economic Education Study Program STKIP PGRI Tulungagung Academic Year 2018/2019 good simultaneously or partially. This research is quantitative research. The population of this study amounted to 112 students. The sample of this study was 56 students using proportional random sampling method. Data collection techniques using the questionnaire method (questionnaire). The results of data analysis in this study indicate: (1) Partially there is a significant effect of personality on the interest in entrepreneurship with tcount (7.129) > t table (2.005) with a significance of 0,000 <0.05. (2) Partially there is a significant effect of entrepreneurial knowledge on the interest in entrepreneurship with tcount (2.032) > t table (2.005) with a significance of 0.047 <0.05. (3) Simultaneously there is a significant influence between personality and entrepreneurial knowledge on the interest in entrepreneurship with Fcount ¬ (55,591)> Ftable ¬ (3.17) with a significance of 0,000 <0.05. Thus it can be concluded that there is an influence of personality and entrepreneurial knowledge on the interest of VIII semester student entrepreneurship in the Economic Education Study Program of STKIP PGRI Tulungagung Academic Year 2018/2019. The results of this study can be used as reference material for future researchers who discuss personal variables and entrepreneurial knowledge of the interest in entrepreneurship. DOI: https://dx.doi.org/10.17977/um014v13i12020p042